Effects of low concentrated BMP-7 administered by co-cultivation or plasmid transfection on human osteoarthritic chondrocytes - Gavénis, Karsten; Schneider, Ulrich; Wallich, Reinhard; Mueller-Rath, Ralf; Schmidt-Rohlfing, Bernhard; Andereya, Stefan (The international journal of artificial organs, 2010)
INTRODUCTION: While BMP-7 has proven to be one of the most potent growth factors in cartilage tissue engineering, protein concentration and route of administration remain a matter of debate. Here we investigated the effects of a low concentration of BMP-7 on human osteoarthritic chondrocytes administered by protein co-cultivation and plasmid transfection. METHODS: Freshly released (P0) or in vitro propagated chondrocytes (P2) were cultivated in a collagen type-I gel for 3 weeks in vitro or in nude mice. Seeded chondrocytes were treated with 50 ng/mL BMP-7 directly added to the medium or were subject to transient BMP-7 plasmid transfection prior to gel cultivation. Untreated specimens served as a control. After recovery, samples were investigated by histological and immunohistochemical staining and real-time PCR. RESULTS: In vitro, collagen type-II protein production was enhanced, and it was stored mainly pericellularly. collagen type-II and aggrecan gene expression were enhanced in both treatment groups. After nude mouse cultivation, col-II protein production was further enhanced, but specimens of the BMP-7 transfection group revealed a clustering of col-II positive cells. Gene expression was strongly upregulated, chondrocyte number was increased and the differentiated phenotype prevailed. In general, freshly released chondrocytes (P0) proved to be superior to chondrocytes pre-amplified in vitro (P2). CONCLUSIONS: Both BMP-7 co-cultivation and plasmid transfection of human osteoarthritic chondrocytes led to improved cartilage repair tissue. Nevertheless, the col-II distribution following BMP-7 co-cultivation was homogeneous, while samples produced by transient transfection revealed a col-II clustering.
Elektronische Reproduktion der Druck-Ausgabe
First Published March 13, 2018
Gesehen am 04.06.2021